2017
DOI: 10.1016/j.bjorl.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone therapy on facial nerve regeneration

Abstract: We found that ozone therapy exerted beneficial effect on the regeneration of crushed facial nerves in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
3
24
0
2
Order By: Relevance
“…Ozbay et al found less vascular congestion and macrovacuolation in the ozone group. Similarly, Somay H et al found less vacuolization, vascular congestion, edema, hemorrhage and fibrosis after ozone therapy [6,21]. In the present study the characteristics of sciatic nerve specimens in the untreated group were similar to those of the treated group (Figure 4.g) except for an increased abundance of schwann cells and cytoplasmic organelles in the treated group.…”
Section: Medical Ozone Therapy Of Sciatic Nerve Cut Injurysupporting
confidence: 84%
See 2 more Smart Citations
“…Ozbay et al found less vascular congestion and macrovacuolation in the ozone group. Similarly, Somay H et al found less vacuolization, vascular congestion, edema, hemorrhage and fibrosis after ozone therapy [6,21]. In the present study the characteristics of sciatic nerve specimens in the untreated group were similar to those of the treated group (Figure 4.g) except for an increased abundance of schwann cells and cytoplasmic organelles in the treated group.…”
Section: Medical Ozone Therapy Of Sciatic Nerve Cut Injurysupporting
confidence: 84%
“…This inadequacy caused by peripheral nerve injuries is related to the type of injury and repair method [1,5]. Oxidative stress can damage peripheric nerve regeneration and the process of repair after nerve cut injury [5][6][7]. The negative im-pacts of free oxygen radicals (FOR) on nerve regeneration can be decreased by antioxidants [7][8][9] Ozone therapy has been developed and it represents a recognized and efficient alternative treatment under specific clinical conditions [10] and has also been suggested as an immunomodulator and activator of cellular metabolism exhibiting long-term anti-inflammatory impacts [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study regeneration of the facial nerve was evaluated by assessing electrophysiological thresholds and by histopathological examination. This proves that ozonetherapy exerted beneficial effect on the regeneration of crushed facial nerves (Ozbay et al, 2016).…”
Section: Neurological Malfunctions (Facial Nerve Paralysis)supporting
confidence: 53%
“…Regeneration and repair process follow nerve injury can be impaired due to the oxidative stress 1,2 . Antioxidants may alleviate the adverse effects of free oxygen radicals on nerve regeneration 3,4 .…”
Section: Introductionmentioning
confidence: 99%